2022
DOI: 10.1111/eci.13856
|View full text |Cite
|
Sign up to set email alerts
|

The fibrosis‐4 score is associated with long‐term mortality in different phenotypes of acute heart failure

Abstract: Background Fibrosis‐4 score (FIB4) was a non‐invasive surrogate to estimate the amount of liver scarring in chronic hepatitis. Considering the presence of increased central venous pressure and congestive hepatopathy in patients with decompensated heart failure, we therefore investigated the prognostic values of FIB4 in acute heart failure (AHF) patients. Method Patients hospitalised primarily for HF were drawn from an intramural registry. FIB4 was calculated according to age, aspartate aminotransferase, alanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…53 The predictive role of the FIB-4 index for mortality in acute HF was investigated in 1854 patients and seemed to be limited to patients with HFpEF (HR per SD: 1.069, 95% CI: 1.047-1.092) and HFmrEF (HR per SD: 1.036, 95% CI: 1.002-1.072), and not of use in HFrEF (HR per SD: 1.005, 95% CI: 0.997-1.012). 54 Yet, if MASLD-related fibrosis apart from fluid overload potently contributes to the exacerbation of acute HF remains to be clarified, especially considering that VCTE-determined liver stiffness was found to decrease along with N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels during hospitalization in patients with acute decompensated HF. 55 This has been substantiated in a study including 877 patients hospitalized for acute HF that separated the cohort based on the reduction of FIB-4 index during hospitalization (low (<1.0%, n = 293), middle (1.0%-27.4%, n = 292), and high (>27.4%, n = 292) reduction of FIB-index).…”
Section: Acute Heart Failurementioning
confidence: 99%
See 3 more Smart Citations
“…53 The predictive role of the FIB-4 index for mortality in acute HF was investigated in 1854 patients and seemed to be limited to patients with HFpEF (HR per SD: 1.069, 95% CI: 1.047-1.092) and HFmrEF (HR per SD: 1.036, 95% CI: 1.002-1.072), and not of use in HFrEF (HR per SD: 1.005, 95% CI: 0.997-1.012). 54 Yet, if MASLD-related fibrosis apart from fluid overload potently contributes to the exacerbation of acute HF remains to be clarified, especially considering that VCTE-determined liver stiffness was found to decrease along with N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels during hospitalization in patients with acute decompensated HF. 55 This has been substantiated in a study including 877 patients hospitalized for acute HF that separated the cohort based on the reduction of FIB-4 index during hospitalization (low (<1.0%, n = 293), middle (1.0%-27.4%, n = 292), and high (>27.4%, n = 292) reduction of FIB-index).…”
Section: Acute Heart Failurementioning
confidence: 99%
“…Therefore, the determination of liver stiffness using NITs in acute HF could predict short‐term prognosis 53,54,56,57 and can help inform about adequate venous decongestion prior to discharge 58,59 …”
Section: Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…Growing clinical evidence revealed that liver fibrosis is a main determinant of outcomes or all-cause mortality in liver disease ( 1 6 ). Metabolic dysfunction–associated steatotic liver disease (MASLD), previously known as nonalcoholic fatty liver disease (NAFLD), could progress to metabolic dysfunction–associated steatohepatitis (MASH), previously known as nonalcoholic steatohepatitis (NASH), accompanied with liver fibrosis occurrence ( 7 ).…”
Section: Introductionmentioning
confidence: 99%